2, 5‐Difluorenyl‐Substituted Siloles for the Fabrication of High‐Performance Yellow Organic Light‐Emitting Diodes. Issue 7 (8th January 2014) - Chen, Bin; Jiang, Yibin; Chen, Long; Nie, Han; He, Bairong; Lu, Ping; Sung, Herman H. Y.; Williams, Ian D.; Kwok, Hoi Sing; Qin, Anjun; Zhao , Zujin; Tang , Ben Zhong
Abstract 2, 3, 4, 5‐Tetraarylsiloles are a class of important luminogenic materials with efficient solid‐state emission and excellent electron‐transport capacity. However, those exhibiting outstanding electroluminescence properties are still rare. In this work, bulky 9, 9‐dimethylfluorenyl, 9, 9‐diphenylfluorenyl, and 9, 9′‐spirobifluorenyl substituents were introduced into the 2, 5‐positions of silole rings. The resulting 2, 5‐difluorenyl‐substituted siloles are thermally stable and have low‐lying LUMO energy levels. Crystallographic analysis revealed that intramolecular π–π interactions are prone to form between 9, 9′‐spirobifluorene units and phenyl rings at the 3, 4‐positions of the silole ring. In the solution state, these new siloles show weak blue and green emission bands, arising from the fluorenyl groups and silole rings with a certain extension of π conjugation, respectively. With increasing substituent volume, intramolecular rotation is decreased, and thus the emissions of the present siloles gradually improved and they showed higher fluorescence quantum yields (ΦF=2.5–5.4 %) than 2, 3, 4, 5‐tetraphenylsiloles. They are highly emissive in solid films, with dominant green to yellow emissions and good solid‐state ΦF values (75–88 %). Efficient organic light‐emitting diodes were fabricated by adopting them as host emitters and gave high luminance, current efficiency, and power efficiency of up to 44 100 cd m−2, 18.3 cd A−1, and 15.7 lm W−1, respectively. Notably, a maximum external quantum efficiency of 5.5 % was achieved in an optimized device.